Experimental Investigation on LPG + Diesel Fuelled Engine with DEE Ignition Improver. (2017) - Vinoth, T.; Vasanthakumar, P.; Krishnaraj, J.; ArunSankar, S.K.; Hariharan, J.; M.Palanisamy,
Abstract: Manufacturing and utilizing biodiesel for transportation is one approach for sustainable energy future for the world. The opportunity to take place of cleaner burning biodiesel fuels for automotive service has drawn increasing attention during the last decade. A biodiesel fuel contributes lesser global climate change. In a dual fuel engine a main fuel that is generally gaseous fuel is mixed with air, compressed and ignited by a small quantity of pilot spray of diesel as in a diesel engine. Dual fuel engines are capable of generating as much power when running with a gaseous fuel as a primary fuel as when operating liquid fuel only. LPG (Liquefied Petroleum Gas) has been widely used as an alternative fuel for petrol and diesel vehicles in light of clean fuel and multiplicity of energy resources. The phenomenon of knock in a dual-fuel engine is the nature of auto ignition of gaseous mixture in the neighbourhood of injected spray. In this paper, using of liquefied petroleum gas (LPG) as a primary fuel with diethyl ether (DEE) as an ignition enhancer in a direct injection diesel engine. The performance and emission characteristics of the LPG– diesel dual-fuel engine performance, emission characteristics are studied and the dual fuel diesel engine results are compared and analysed.